(untitled) (Research, Society and Development, 2021)
The objective of this study was to outline the epidemiological profile of abortions in the State of Alagoas - Brazil in the temporal cut - off (2006-2016). Abortion causes the interruption of 10% to 31% of pregnancies, deserving a prominence within epidemiology, presenting as one of the major causes of maternal death in the world, especially in developing countries. This is a quantitative, retrospective, exploratory study, in which the data were collected in the Datasus/Tabnet/Ministry of Health. Although the submission to the Ethics Committee was not used, ethical precepts were respected, based on National Health Council Resolution 466/2012. The study variables were: mother’s age, marital status, education level and color / race. The results showed: When the age group was analyzed, the greatest number was 131 miscarriages at ages between 15 and 19 years; Regarding marital status, the expressive number was 245 in single women; According to the educational level, 165 abortions were registered in women with 4 to 7 years of schooling. Regarding the color / race variable, the study showed that the largest number of abortions occurred in 371 brown women. Thus, the data demonstrate that there is a lot of underreporting of the cases and that nursing must every day act, in addition to technical procedures based on ethical and humanitarian principles, seeking in this way an adequate treatment, thus taking care of these women with full perspective, because many do not seek proper care due to fear and insecurity.